The language of life DNA and the revolution in personalized medicine - Collins, Francis S. (Harper, 2010)
A medical revolution is upon us, and leading geneticist Collins explains its dimensions here. Our knowledge of the genetic basis for disease has increased exponentially in recent years, and we are now able to understand and treat diseases at the molecular level with personalized medicine--care based on an individual's genetic makeup. Collins presents cutting-edge science for lay readers who want to take control of their medical lives. He discusses cancer, obesity, aging, racial differences, and a host of other concerns, as well as the medical advances directly attributable to the Human Genome Project. He is also not shy about taking on large political issues: he points out problems with our current health-care system, discusses stem-cell research, and in a cogent commentary, recommends--with caveats--direct-to-consumer DNA testing. He does a superb job of humanizing a complex scientific and medical subject.--From publisher description.